Short-term assessment of pain and discomfort during rapid maxillary expansion with tooth-bone-borne and tooth-borne appliances: randomized clinical trial - Bruno de Paula Machado PASQUA; Cristiane Barros ANDRÉ; João Batista de PAIVA; José RINO NETO (Dental Press Editora, 2023)
ABSTRACT Objective: The aim of this randomized clinical trial was to evaluate and compare, during the first week of rapid maxillary expansion (RME), the impact caused by two types of appliances: Hyrax and Hybrid Hyrax. Methods: Forty-two patients who met the eligibility criteria (aged 11-14 years, with transverse maxillary deficiency, posterior crossbite, and presence of maxillary first premolars and first permanent molars) were selected and randomly divided into two groups: TBB GROUP (tooth-bone-borne expander), treated with Hybrid Hyrax (12 females and 9 males, mean age 13.3 ± 1.3 years), and TB GROUP (tooth-borne expander), treated with Hyrax (5 females and 16 males, mean age 13.3 ± 1.4 years). Pain and discomfort were assessed in two times: after the first day of activation (T1) and four days after, by means of the numerical rate scale and the instrument MFIQ (Mandibular Functional Impairment Questionnaire). Descriptive statistics and the Mann-Whitney test were used for comparison between groups and between sexes. A 5% significance level was adopted. Results: Both appliances had a negative impact, generating pain and discomfort, and reducing functional capacity. However, the scores obtained were of low intensity and no significant differences were observed between the groups. Considering sexes, there were statistically significant differences, with the female sex presenting higher scores for pain and functional limitation. Conclusions: Despite causing impact in pain and increase in the functional limitation, these changes were of low intensity, with no statistical difference between the groups. Females were more sensitive to the impact caused by the RME.